Numerical Computation of Turbulent Flow Fields in a Fan-stirred Combustion Bomb. Issue 4 (12th March 2021) - Zhang, Feichi; Zirwes, Thorsten; Habisreuther, Peter; Zarzalis, Nikolaos; Bockhorn, Henning; Trimis, Dimosthenis
ABSTRACT: This work presents a numerical study of the initial turbulent flow characteristics prior to ignition in a fan-stirred combustion vessel. The moving mesh methodology has been applied to account for the rotational movement of eight fans mounted within the vessel. The transient, highly-resolved numerical simulations resolve the 3D turbulent flow field in the whole vessel and complement 2D measurements of the flow field. The calculated turbulence intensities yield reasonably good agreement with measured data, showing a nearly linear increase with the rotation speed of the fans ω . The same applies for the spectra of the turbulent kinetic energy. The rms of velocity fluctuations is almost constant and the same in each direction in the core region with a diameter of approx. 2 cm, confirming the homogeneity and isotropy of the generated turbulent flow field in the fan-stirred bomb, as observed in previous experiments. The calculated integral length scale agrees well with the measured value, which increases with ω or the turbulent Reynolds number Ret, respectively. The calculated rates of decay of the Kolmogorov and Taylor lengths with Ret have shown a quantitatively good agreement with the hypothesis proposed by Kolmogorov for isotropic turbulence, which justifies the validity and reliability of the numerical simulations. The present study serves as a reference for assessing the uncertainties given by common 2D measurement techniques, which allows a more accurate analysis of the turbulence characteristics and the turbulence-flame interactions in a fan-stirred combustion vessel.